Stage-dependent prognostic shift in mismatch repair-deficient tumors: Assessing patient outcomes in stage II and III colon cancer - Hestetun, Kjersti Elvestad; Rosenlund, Nina Benedikte; Stanisavljević, Luka; Dahl, Olav; Myklebust, Mette Pernille (Frontiers in Oncology, 2022)
Introduction: Deficient mismatch repair (dMMR) or high microsatellite instability (MSI-H) is associated with an improved prognosis in colon cancer stage II but poor prognosis in stage IV colon cancer. The clinical significance of dMMR in colon cancer stage III is not established. Methods: Tissue microarrays (TMAs) from 544 patients with colon cancer stage II and III with clinicopathological- and survival data were stained for MMR proteins, CD3, CD8 and Programmed Cell Death Ligand-1 (PD-L1) and relations to patient outcomes were reviewed Results: In stage III colon cancer, dMMR was a marker of poor disease-free survival (DFS) (Kaplan Meier, mean survival in months: dMMR: 28.76 (95% CI 18.46-39.05) vs. pMMR 40.91 (37.20-44.63), p=0.014, Multivariate Cox Regression: HR 4.17 (95% CI 2.02-8.61), p<0.001). In stage II colon cancer, there was a tendency towards improved DFS for dMMR patients (dMMR: 57.14 (95% CI 54.66-59.62) vs. pMMR 53.54 (95% CI 51.48-55.60), p=0.015, Multivariate Cox Regression HR 0.24 (95% CI 0.06-1.04), p=0.057). CD3, CD8 and PD-L1 expression was not associated with prognosis of dMMR patients. Multivariate Cox Regression analysis showed a significant interaction between MMR phenotype and stage (p=0.001). Conclusion: dMMR is associated with an improved prognosis in stage II colon cancer but is no longer associated with a favorable prognosis in stage III colon cancer.